Karakteristik Edible Film Pati Sagu Alami dan Pati Sagu Fosfat dengan Penambahan Gliserol - Febby Jeanry Polnaya; La Ega; Devidson Wattimena (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2016)
The purpose of this study was to evaluate the effect of the addition of several glycerol concentrations in the making of edible film from native and phosphate sago starch on physical, mechanical and barrier properties of the film. A completely randomized experimental design was applied in this study consisting of two factors of treatments, i.e.: native and phosphate sago starch, and the second factor was glycerol concentration with three levels of treatments, i.e.: 0.5, 1.0, and 1.5 % (w/w). The films were characterized for tensile strength, elongation, solubility, transparency, and water vapor transmission rate. Edible films have produced characteristics for tensile strength from 3.05 to 31.49 MPa, elongation from 3.03 to 20.94 %, solubility from 33.44 to 42.43 %, transparency from 0.59 to 4.14 %, and water vapour transmission rate from 7.76 to 15.80 g/m2.h. Glycerol was found to affect the increase of elongation, solubility, and water vapour transmission rate, as well as the decrease of its tensile strength and transparancy. The films made from sago starch phosphate showed to increase the solubility and to have significant effect compared with native sago starch, but not affecting the other properties. ABSTRAKTujuan penelitian ini adalah untuk mempelajari pengaruh penambahan beberapa konsentrasi gliserol pada pembuatan edible film dari pati sagu alami dan pati sagu fosfat terhadap sifat fisik, mekanik dan barrier film. Rancangan yang digunakan adalah rancangan acak lengkap yang terdiri dari dua faktor yaitu perlakuan jenis pati sagu dengan dua taraf perlakuan yaitu: pati sagu alami dan pati sagu fosfat dan tiga taraf konsentrasi gliserol yaitu: 0,5, 1,0 dan 1,5 % (b/b). Peubah yang diamati adalah tensile strength¸ elongasi, daya larut, transparansi, dan laju transmisi uap air. Karakteristik edible film yang dihasilkan meliputi tensile strength adalah 3,05 - 31,49 MPa, elongasi 3,03 - 20,94 %, daya larut 33,44 - 42,43 %, transparansi 0,59 - 4,14 %, dan laju transmisi uap air 7,76 - 15,80 g/m2.jam. Penambahan gliserol menyebabkan elongasi, daya larut, dan laju transmisi uap air meningkat, tetapi tensile strength dan transparansinya menurun. Perlakuan pati sagu fosfat hanya menyebabkan daya larut film meningkat, tetapi tidak untuk sifat-sifat film lainnya.